Identification of protein biomarkers in host cerebrospinal fluid for differential diagnosis of tuberculous meningitis and other meningitis - Huang, Mailing; Ding, Zeyu; Li, Wensheng; Chen, Weibi; Du, Yadong; Jia, Hongyan; Sun, Qi; Du, Boping; Wei, Rongrong; Xing, Aiying; Li, Qi; Chu, Naihui; et al. (Frontiers in Neurology, 2022)
Background and purpose: The diagnosis of tuberculous meningitis (TBM) is difficult due to the lack of sensitive methods. Identification of TBM-specific biomarkers in the cerebrospinal fluid (CSF) may help diagnose and improve our understanding of TBM pathogenesis. Patients and methods: Of the 112 suspected patients with TBM prospectively enrolled in the study, 32 patients with inconclusive diagnosis, non-infectious meningitis and long-term treatment with hormones and immunosuppressants, were excluded. The expression of 8 proteins in the CSF were analyzed using ELISA in 22 patients with definite TBM, 18 patients with probable TBM and 40 non-TBM patients. Results: Significant differences in the expression of 7 proteins were detected between the TBM and non-TBM groups (P < 0.01). Unsupervised hierarchical clustering (UHC) analysis revealed a disease-specific profile consisting of 7 differentially expressed proteins for TBM diagnosis, with an accuracy of 82.5% (66/80). Logistic regression with forward stepwise analysis indicated that a combination of 3 biomarkers (APOE_APOAI_S100A8) showed a better ability to discriminate TBM from non-TBM patients [AUC = 0.916 (95%CI: 0.857 – 0.976)], with a sensitivity of 95.0% (95%CI: 83.1% – 99.4%) and a specificity of 77.5% (95%CI: 61.5% – 89.2%). Conclusions: Our results confirmed the potential ability of CSF proteins to distinguish TBM from non-TBM patients, and provided a useful panel for the diagnosis of TBM.